Morphometric aspects of studying the features of remodeling of atrial structures at postresection portal hypertension - N. Gdanska; M. Hnatjuk; L. Tatarchuk; N. Monastyrska (Kazimierz Wielki University, 2021)
Introduction. Removal of the left and right lateral lobes of the liver in white rats leads to postresection portal hypertension, which is characterized by dilation and plethora of the hepatic portal vein, mesenteric veins, esophageal and gastric veins, veins of the anterior abdominal wall, splenomegaly, ascites and multiorgan failure. Objective of the research: to study the features of remodeling of the structures of the atria at postresection portal hypertension histostereometrically. Materials of the research and their discussion. The peculiarities of remodeling the structures of the atria were histostoreometrically studied in 65 adult white male rats, which were divided into 3 groups: the 1- consisted of 20 intact animals, the 2 - 30 rats with postresection portal hypertension, which was modeled by removal of the left and right lateral lobes of the liver, the 3 - 15 animals with postresection portal hypertension and multiorgan failure. One month after the start of the experiment, rats were euthanized by bloodletting under conditions of thiopental anesthesia. Histological micropreparations were used to determine the diameters of cardiomyocytes of the left and right atria, diameters of their nuclei, nuclear-cytoplasmic relations, relative volumes of cardiomyocytes, capillaries, stroma, stromal-cardiomyocyte, capillary-cardiomyocyte relations, relative volumes of damaged cardiomyocytes. Quantitative indicators were processed statistically. Results of the research and their discussion. Histostereometrically, it was found that postresection portal hypertrophy leads to hypertrophy of atrial cardiomyocytes, their nuclei, growth of stromal structures, relative volumes of damaged cardiomyocytes, disorders of tissue and cellular structural homeostasis. The revealed features of remodeling of the studied structures dominated in the left atrium at combination of postresection portal hypertension with multiorgan failure. Conclusions. Postresection portal hypertension leads to pronounced remodeling of the structures of the left and right atria, characterized by hypertrophy of cardiomyocytes, changes in their nuclear-cytoplasmic relations, an increase of the relative volume of stroma, damaged cardiomyocytes, pronounced disorders of tissue and cellular structural  homeostasis. The revealed morphological changes dominated in the left atrium at combination of postresection portal hypertension with multiorgan failure.